Rancang Bangun Sistem Booking Foto Studio Berbasis Web Menggunakan Metode Agile - Angga Kurnia; Stevianus Imanuel Salangka; Unggul Prasetyo Utomo; Saprudin (Shofanah Media Berkah, 2023)
Photo studio is a place that is sought after by many people to capture important moments in their lives. Along with technological developments, the use of a Booking system is becoming increasingly important to make it easier for customers to book photo schedules, one of which is the Hey Studio photo studio. The photo studio Booking process so far still uses a manual method, when Booking still uses a form by coming directly to the studio, with this website technology it is hoped that it can help customers to book with a range that is far from Hey Studio photo studio. This study aims to develop a Booking system software at a photo studio using the agile method. The software development method used is Agile Scrum, which consists of several stages, such as sprint planning, daily scrum, sprint review, and sprint retrospective. Software development is carried out by considering user needs and business goals, by prioritizing iteration and iterative testing. In addition, the integration of the Booking system with other information systems is also considered. The results of this study are expected to contribute to the development of a Booking system at a photo studio with agile methods. In addition, the results of this research are also expected to help the manager of Hey Studio photo studio in improving their productivity and quality of service.